2014
DOI: 10.1177/1470320313507123
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of aliskiren and valsartan in mice with diabetic nephropathy

Abstract: Aim: We investigated whether aliskiren, a direct renin inhibitor, provided protection in a model of diabetic nephropathy in mice and compared its protective effects to valsartan, an angiotensin II type 1 receptor blocker. Materials and methods: Hyperglycemia was induced with streptozotocin (STZ, 40 mg/kg/day × 5 days) injection in DBA/2J mice fed on a high fat diet. Mice were treated with either aliskiren (25 mg/kg/day) or valsartan (8 mg/kg/day) for 6 weeks. Results: Aliskiren and/or valsartan treatment signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…In contrast in rodent diabetic kidney disease low dose irbesartan reduces albuminuria and inflammation, but does not reduce ER stress (calnexin and GRP78/BiP staining) [200]. Valsartan (an ARB) and aliskiren (direct renin inhibitor) also reduce CHOP and XBP-1 expression in rodent diabetic kidneys [201]. Thus the beneficial effects of renin-angiotensin system blockade, may be in part related to modulation of ER stress.…”
Section: Modulation Of Er Stressmentioning
confidence: 99%
“…In contrast in rodent diabetic kidney disease low dose irbesartan reduces albuminuria and inflammation, but does not reduce ER stress (calnexin and GRP78/BiP staining) [200]. Valsartan (an ARB) and aliskiren (direct renin inhibitor) also reduce CHOP and XBP-1 expression in rodent diabetic kidneys [201]. Thus the beneficial effects of renin-angiotensin system blockade, may be in part related to modulation of ER stress.…”
Section: Modulation Of Er Stressmentioning
confidence: 99%
“…Aliskiren, the only available orally effective DRI, has been demonstrated to be effective in blood pressure reduction and end-organ protection, such as cardiovascular and renal protection in preclinical and clinical experiments. In addition, aliskiren has been shown to protect kidneys from acute kidney injuries induced by either contrast (23) or ischemia-reperfusion (17,50) or by chronic kidney diseases (e.g., in diabetic nephropathy) (22,49) as well as by doxorubicin-induced nephrotoxicity (39). Aliskiren alone or in combination with other drugs has also been shown to attenuate renal fibrosis and inflammation induced by ureteral obstruction (8,42,52).…”
mentioning
confidence: 99%
“…Several studies have also demonstrated that blockade of the RAS attenuates the expression of an array of cytokines and growth factors with important roles in the impairment of renal functions in rats with unilateral ureteral obstruction (UUO) (8,18,52). Currently, drugs targeting the RAS, including direct renin inhibitors (DRIs), ACE inhibitors, ARBs, and aldosterone blockers have been most widely used for slowing or preventing renal damage in chronic kidney diseases (49).…”
mentioning
confidence: 99%
“…Studies shows that the renin inhibitor (aliskiren) ameliorates renal damage in diabetic TG (mREN-2) rats (Kelly et al, 2007; Feldman et al, 2008) or in type 1 or 2 diabetics (Parving et al, 2008; Wang et al, 2014). ACE inhibitors (ACEI) or AT1 receptor antagonists reduce mesangial sclerosis and proteinuria in animal models of both type 1 and type 2 diabetes (Andersen et al, 2000; Chan et al, 2000; Lewis et al, 2001; Brenner et al, 2001; Lewis, 2002; Carey and Siragy, 2003).…”
Section: The Renin Angiotensin System (Ras) and Dnmentioning
confidence: 99%